A hermenêutica política da esperança de Jürgen Moltmann em diálogo com a espiritualidade neoprotestante brasileira : o binômio saúde e doença como um novo paradigma hermenêutico de teologicidade - Pires, Anderson Clayton (2007)
The central subject of this thesis is the escathological hope. Through a Historic-Biblical research, the author of this thesis searchs to identify the meaning that the concepts tiqwah and elpis had for their Jewish-Christians receivers originary. Jürgen Moltmann, when propose a politic of hope hermeneutic searchs to retake this subject leaving from the contexts in which it has originated. All the Christian hope conception developed by Moltmann has its unfoldings in the public dimension of the Christian´s mission in the world. Therefore, the escathological hope produces an ethology that it is proper to itself. In it, the hope is instrumentalized by the faith that assumes the world as locus of transformer action, becoming, through the practical of love, the cosmo-anthropologycal redemption a reachable possibility in the efetivation of the ethical principles of justice and truth. In this direction, in the ethology of hope, the other becomes reference of the missio spei, and it´s for it, as a part of a bigger reality (kósmos), that the redentive meaning of escathological history is directed teleologically. It is to the future that the eschatological hope projects its look and desires to see its uthopy carry through fully. Already the binomial health-disease as new hermeneutic paradigm of teologicity of Brazilian neoprotestantism, conceives the hope in a different soteriologic contour, in which the lived present, here-now , is understood as the locus where the historical dimension of the believer`s salvation materializes. The integral cure of the anthrôpos is the forceful sign that the Biblical soteria has, in the immediate historical dimension, its psychosomatic meaning completely confirmed. It´s for this éon that the neoprotestant look of faith search its integral auto-accomplishment. In this direction, the neoprotestant spirituality develops a desescathologized ethology that affirms the transcendence of this world and loses of its hermeneutic horizon the futuric dimension of the eschatological hope such as if it praised in the protochristianism. However, the possibility to establish a constructive dialogue enters these two faith epistemologies: the moltmannian and the Brazilian neoprotestant exists. Finding this point in common it´s the task that the author of this thesis proposes to satisfy.